Antioxidative Activity of Colostrum and Human Milk: Effects of Pasteurization and Storage. Issue 6 (June 2016) - Marinković, Vesna; Ranković-Janevski, Milica; Spasić, Snežana; Nikolić-Kokić, Aleksandra; Lugonja, Nikoleta; Djurović, Dijana; Miletić, Srdjan; Vrvić, Miroslav M.; Spasojević, Ivan
ABSTRACT: Objectives: Milk banks collect, pasteurize, and freeze/store human milk. The processing may alter redox properties of milk, but the effects have not been fully examined. Methods: We collected 10 mature milk and 10 colostrum samples and applied a battery of biochemical assays and electron paramagnetic resonance spectroscopy to inspect changes that milk undergoes with pasteurization and 30 days storage at −20°C. Results: Pasteurization and storage of raw milk did not affect total nonenzymatic antioxidative capacity, but specific components and features were altered. Urate radical and ascorbyl radical emerge as products of exposure of milk to hydroxyl radical-generating system. Processing shifted the load of antioxidative activity from ascorbate to urate and lowered the capacity of milk to diminish hydroxyl radical. Pasteurization caused a significant drop in the activity of 2 major antioxidative enzymes—superoxide dismutase and glutathione peroxidase, whereas freezing/storage of raw milk affected only superoxide dismutase. Colostrum showed drastically higher total nonenzymatic antioxidative capacity, hydroxyl radical scavenging ability, and glutathione reductase activity compared with mature milk. Conclusions: Pasteurization and storage affect nonenzymatic and enzymatic antioxidative agents in human milk. It appears that nonenzymatic antioxidative systems in colostrum and milk are different. The effects of processing may be partially compensated by fortification/spiking with ascorbate before use.